2012
DOI: 10.1016/j.devcel.2012.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Hoxd13 Contribution to the Evolution of Vertebrate Appendages

Abstract: Fossil data suggest that limbs evolved from fish fins by sequential elaboration of their distal endoskeleton, giving rise to the autopod close to the tetrapod origin. This elaboration may have occurred by a simultaneous reduction of the distal ectodermal fold of fish fins. Modulation of 5'Hoxd gene transcription, through tetrapod-specific digit enhancers, has been suggested as a possible evolutionary mechanism involved in these morphological transformations. Here, we overexpress hoxd13a in zebrafish to investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
101
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(111 citation statements)
references
References 54 publications
10
101
0
Order By: Relevance
“…Further, ectopic expression of Hoxd13a in the distal fin enhances proliferation, distal expansion of chondrogenesis and reduction in fin-folding [50]. These findings support the idea that additional cis-regulatory elements in the tetrapod lineage, perhaps including the tetrapod-specific CsC, served to modify a preexisting and conserved gene regulatory network in the distal fin/limb bud.…”
Section: Origin Of the Tetrapod Autopodsupporting
confidence: 72%
“…Further, ectopic expression of Hoxd13a in the distal fin enhances proliferation, distal expansion of chondrogenesis and reduction in fin-folding [50]. These findings support the idea that additional cis-regulatory elements in the tetrapod lineage, perhaps including the tetrapod-specific CsC, served to modify a preexisting and conserved gene regulatory network in the distal fin/limb bud.…”
Section: Origin Of the Tetrapod Autopodsupporting
confidence: 72%
“…Studies have shown that the repeated experimental removal of the AEF from zebrafish fin buds results in increased mesenchymal cell proliferation and excessive elongation of the mesenchyme, suggesting that prolonged exposure to AER signals induces distal elongation of mesenchyme and the endoskeleton (Yano et al, 2012). By contrast, overexpression of the distal hoxd13a gene in fin buds reduces the size of the AEF and distal expansion of chondrogenic tissue (Freitas et al, 2012). Two rows of rigid fibrils called actinotrichia keep the AEF straight, and the knockdown of two genes essential for their formation, actinodin1 and -2 (and1/2), results in a defective AEF (Zhang et al, 2010a).…”
Section: Molecular Insights Into the Fin-to-limb Transitionmentioning
confidence: 99%
“…This step, along with the repression of Hoxa11 by Hoxa13, leads to the two-phase, bimodal regulation described at the HoxD locus (Sheth et al 2014;Woltering et al 2014). Such a bimodal regulation allowed the self-enhanced transcription of Hoxd13, which, like Hoxa13, has the ability to stimulate growth and produce cartilage models and long bones of reduced size (Yokouchi et al 1995a;Freitas et al 2012), leading to digits. This also provided the mechanistic opportunity to offset the two domains of transcription and, as a consequence, produce the mesopodial articulation (Villavicencio-Lorini et al 2010;Woltering and Duboule 2010;Andrey et al 2013).…”
Section: Evolution Of Hox Regulation In the Transformation Of Paired mentioning
confidence: 99%